PEMANFAATAN ECENG GONDOK UNTUK MENURUNKAN KADAR DETERJEN DI DALAM AIR - Dedi Putri Purwati; Ferry Kriswandana; Bambang Sunarko (GEMA LINGKUNGAN KESEHATAN, 2015)
Detergent is included as chemical characteristic of the wastewater in the form of organic compound that has negative impact on the enviroment and human health. Phytoremediation can be used to reduce level of detergent by using the water hyacinth plant as abssorbent. The purposeof this research is to use water hyacinth to reduce level of detergent in water. This is a pre-experimental research with one group pretest-posttest approach. Datacollection was conducted by checking detergent level for a contact time as many as 31 samples.Furthermore, the data was analyzed descriptively by using tabulation. The highest percentage of decrease in detergent level based on the amount of water hyacinth was in the 6th day with 6 hyacinth by 70.08%. In this research, it is advisable to raw water companies to use water hyacinth in reducing level of detergent in water. Other researchers are suggested to increase the amount of water hyacinth and extend contact time by performing the same processing. To add detergent, it needs to take into account the initial detergent concentration.